ANALYSIS OF THE IMPLEMENTATION OF THE BALANCED SCORECARD METHOD TO DETERMINE THE DEVELOPMENT OF TEMPE COMPANY PERFORMANCE - Purwanti, Ari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to examine the balanced scorecard method's implementation in order to ascertain the tempe company's performance development. This study used the crossectional survey method, which entails concurrently approaching, watching, and collecting data on risk variables and their consequences. The questionnaire utilized a Likert scale and was processed using a variety of testing methodologies, including validity testing, reliability testing, and regression testing. Based on the study results, it can be concluded that the variables Financial Perspective, Customer Perspective, Internal Business Processes Perspective, Learning & Growth Perspective influence Company Performance.